As marcas de interpessoalidade em uma coluna de opinião política - Cabral, Sara Regina Scotta (Linguagens & Cidadania, 2017)
Studies in Systemic Functional Linguistics have been revealing a wide range of possibilities to investigate textual genres. This article aims to analyze the interpersonal metafunction of a text published in Folha de São Paulo, written by Eliane Cantanhêde in 2003. The text was decomposed into paragraphs and sentences, which were distributed into Mood and Residue. We observed the modal adjuncts and some metadiscursive operators, which contribute to reinforce interpersonal metafunction. The results point to the construction of an ethos sure of its opinion, in which declarative clauses are more usual than exclamative ones. Intensifiers and evaluatives in Residue were used by the columnist to express judgment on the facts in question. The polarity of the Mood appeared to be positive and few metaphors were used. Few commands and exclamations, as well as a few points of view in the first person, are present in the texts.